Analysis of Leachate Quality Status, Rainfall Intensity and Pollution Index at the Final Processing Site of Talumelito Waste - Warow, Novalia; Mahmud, Marike; Lihawa, Fitryane (International Journal Papier Advance and Scientific Review, 2025)
This study aims to analyze the quality of leachate based on quality standards, examine the relationship between rainfall intensity and leachate quality, and assess the level of leachate pollution at the Talumelito TPA. The research employs a descriptive quantitative approach by collecting primary and secondary data. Primary data were obtained from leachate sample testing, while secondary data included rainfall intensity from the Gorontalo Climatology Station. The leachate samples, taken from the inlet and outlet of the reservoir on December 11, 2024, were tested for pH, BOD, COD, TSS, N-Total, Mercury, and Cadmium at LPPT UGM Yogyakarta and the UPTD Regional Health Laboratory Center of Gorontalo Province. The results indicate that from 2022 to 2024, five parameters at the inlet (pH, BOD, COD, TSS, N-Total) and four at the outlet (BOD, COD, TSS, N-Total) exceeded the quality standards set by PerMenLHK No. 59 of 2016. However, Mercury and Cadmium at the inlet and pH, Mercury, and Cadmium at the outlet met the standards. Rainfall intensity ranged from 9 mm (2023) to 235 mm (2022), but it did not significantly impact the leachate quality. Pollution index analysis using the IP and Storet methods showed an average IP value of 4.2, indicating light pollution, while the Storet classification placed the water quality in Class C (-18), meaning moderate pollution. These findings highlight the need for improved leachate treatment and management to mitigate environmental impacts at Talumelito TPA.